Asian Games Sports Complex - Chua, Edward B.; Kee-Tian Kho Jeng.; Tiotuyco, Victor N.; Commandante, Armand S. (1983)
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman.
Vita.
Keywords: Sports facilities -- Designs and plans; Sports complexes